Variables Associated With Inpatient and Outpatient Resource Utilization Among Medicare Beneficiaries With Nonalcoholic Fatty Liver Disease With or Without Cirrhosis - Sayiner, Mehmet (J Clin Gastroenterol, 2017)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is one of the leading causes of chronic liver disease worldwide with tremendous clinical burden. The economic burden of NAFLD is not well studied. GOAL: To assess the economic burden of NAFLD. STUDY: Medicare beneficiaries (January 1, 2010 to December 31, 2010) with NAFLD diagnosis by International Classification of Diseases, Ninth Revision codes in the absence of other liver diseases were selected. Inpatient and outpatient resource utilization parameters were total charges and total provider payments. NAFLD patients with compensated cirrhosis (CC) were compared with decompensated cirrhosis (DC). RESULTS: A total of 976 inpatients and 4742 outpatients with NAFLD were included—87% were white, 36% male, 30% had cardiovascular disease (CVD) or metabolic syndrome conditions, and 12% had cirrhosis. For inpatients, median total hospital charge was $36,289. NAFLD patients with cirrhosis had higher charges and payments than noncirrhotic NAFLD patients ($61,151 vs. $33,863 and $18,804 vs. $10,146, P<0.001). Compared with CC, NAFLD patients with DC had higher charges and payments (P<0.02). For outpatients, median total charge was $9,011. NAFLD patients with cirrhosis had higher charges and payments than noncirrhotic NAFLD patients ($12,049 vs. $8,830 and $2,586 vs. $1,734, P<0.001). Compared with CC, DC patients had higher total charges ($15,187 vs. $10,379, P=0.04). In multivariate analysis, variables associated with increased inpatient resource utilization were inpatient mortality, DC, and CVD; for outpatients, having CVD, obesity, and hypertension (all P<0.001). CONCLUSIONS: NAFLD is associated with significant economic burden to Medicare. Presence of cirrhosis and CVD are associated with increased resource utilization.